THE INFLUENCE OF AN URBAN PARK IN BARBOSA FERRAZ, PARANÁ, ON THE PRACTICE OF PHYSICAL ACTIVITY (Interdisciplinary Studies Journal, 2026)
This study aims to outline the profile of an urban park and the level of physical activity of its users, taking as a case study Parque Verde Vida, the main public leisure and sports space in Barbosa Ferraz (PR), recognized for its active and daily use. The research is characterized as quantitative, descriptive and observational, based on a bibliographic review and on-site data collection through systematic observation. The System for Observing Play and Recreation in Communities (SOPARC) was applied to record patterns of use of the space, and the International Physical Activity Questionnaire (IPAQ) - short version, aimed at assessing the level of physical activity of 62 individuals (19 to 91 years old). The results showed a predominance of female users (66.1%), with a greater concentration of age between 60 and 79 years old (43.5%), whose peak frequency occurred at 8 am and 6:30 pm. Regarding the classification of physical activity level, a high prevalence of "very active" individuals (88.7%) was identified, with no sedentary individuals (0%) and only one participant categorized as "irregularly active B" (1.6%). The findings suggest that the park plays a significant role in promoting active habits, especially among women and the elderly, with greater use in the morning. However, it is necessary to improve the park's infrastructure, such as expanding equipment and offering guided programs, aiming to enhance its use as a public health tool. The data reinforce the relevance of urban policies that integrate green spaces with the promotion of healthy lifestyles in municipal contexts.
Keywords: Sedentary Behavior; Green Areas; Physical Exercise; Quality of Life